Atividade sindical e situações de trabalho: uma história de vida - Valadao, Kleyton Teixeira (2019)
The objective of this dissertation was to understand, from an ergological perspective, what the life history of a union member has to reveal about union activity. The world of work scenario from the 1980s onwards shows radical changes in work processes, consumer habits, geographical and geopolitical configurations, and consequently changes in state powers and practices. Coupled with neoliberal logic, there was a predatory search for profitability and accumulation, and the result was job degradation and dehumanization (HARVEY, 1992). The Washington Consensus, a set of neoliberal economic formulations, was marked by recommending to countries aligned with economic deregulation, liberalization of interest and exchange rates, review of public spending priorities, greater openness to foreign direct investment and strengthening of law. property (TORRES, 2000). The consequence was the attack on the national constitution of several countries, especially those most economically and politically vulnerable, to reform it and make it more receptive to the interest of external capital and the national state that should prevent or alleviate legal constraints on capital movements, became a mere guarantor of the thesis of free trade and external capital (SILVA; SALIBA, 2015). In labor relations, the result was an escalation against labor rights, subjecting workers to instability, informality, unhealthiness, dangerousness and unemployment (ANTUNES, 2011, 2015). In Brazil, such events favored on the one hand the emergence of a neoliberal unionism, expression of the new right and the conservative world wave, such as Força Sindical, on the other, the inflection of the CUT, which seemed not prepared for this moment of transition, failing to elaborate and propose economic alternatives contrary to the existing pattern of capitalist development in Brazil (ANTUNES, 2002). This dissertation sought to shed light on the activity of the trade unionist in his daily struggle against the precariousness of work, and for this purpose the life history method was adopted as the methodological path. The intervention of Ergology as a theoretical lens aimed to encourage those who live and work to put into words a point of view about its activity, in order to make it communicable and subject it to the confrontation of knowledge (SCHWARTZ, 2011). Juvenal's life story evidences, by his own accounts, the conflicts, the debates about norms and values, the use of the self-body by himself and others, the tensions between the three spheres, 1) trade unionism, 2) market and 3) State. It has been demonstrated how life history can be used as an ergological device to call the worker to produce knowledge about his own existence, including in his work, and to give voice to certain groups so that they can tell their stories according to their needs. prospects. Juvenal's life story can also represent the life stories of many brazilians who fight for the right to live fully through decent work.